2022
DOI: 10.1097/gme.0000000000001920
|View full text |Cite
|
Sign up to set email alerts
|

Declining serum bone turnover markers are associated with the short-term positive change of lumbar spine bone mineral density in postmenopausal women

Abstract: Objective: While serum bone turnover markers (BTMs) and bone mineral density (BMD) have been confirmed as useable risk assessment tools for postmenopausal osteoporosis, the associations between BTMs and BMD changes are still ambiguous. The aim of this study was to explore the underlying associations between BTMs and BMD changes in postmenopausal women. Methods: Between January 2015 and October 2020, 135 postmenopausal women were retrospectively enrolled. They were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(102 reference statements)
0
6
0
1
Order By: Relevance
“…As a direct reflection of the changes in bone homeostasis, the re-review of bone turnover markers (BTMs) in recent years seems to provide new hope for the auxiliary diagnosis of PMOP [ 8 , 9 ]. However, recent studies, including our own, have confirmed that there is a limited correlation between the level of serum BTMs and BMD changes [ 10 , 11 ]. Regretfully, few convenient and accurate biomarkers are currently available for diagnosis in the clinic.…”
Section: Introductionmentioning
confidence: 93%
“…As a direct reflection of the changes in bone homeostasis, the re-review of bone turnover markers (BTMs) in recent years seems to provide new hope for the auxiliary diagnosis of PMOP [ 8 , 9 ]. However, recent studies, including our own, have confirmed that there is a limited correlation between the level of serum BTMs and BMD changes [ 10 , 11 ]. Regretfully, few convenient and accurate biomarkers are currently available for diagnosis in the clinic.…”
Section: Introductionmentioning
confidence: 93%
“…ALP, N-MID, and β-CTX are markers of bone formation and resorption, which can be easily detected and directly reflect the change in bone metabolism before bone morphological change ( 14 , 21 ). β-CTX is a C-terminal cross-linked peptide of type I collagen, which is produced in the process of collagen decomposition and can be used to indirectly reflect the function and activity of osteoclasts in the skeletal system ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…N-MID is the hydrolytic fragment of osteocalcin secreted by osteoblasts and can be used to reflect the process of bone formation. The declining N-MID and β-CTX were significantly associated with a short-term positive change in Lumber spine 1-4 BMD of postmenopausal women over 1 year ( 14 ). ALP is a group of glycoproteases that can hydrolyze phosphates under alkaline conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk calculators (FRAX®), using clinical risk factors and calculating the 10 year probability of fracture, could effectively predict the hip fracture when combined with BMD, but are complex and limited in predicting the risk of other fractures, especially for OVCF, because the circumstances leading to OVCF are frequently controversial and unknown. 3 , 6 , 12 , 13 In addition to BMD and bone turnover markers (BTM), 14 previous studies also reported that serum albumin, 15 serum cholesterol level, 16 and lumbar muscle mass 17 were associated with osteoporotic fractures. Moreover, a previous study had shown that OVCFs were related to frailty, and conversely, frailty was further worsened after OVCFs due to the deficit accumulation being greater.…”
Section: Introductionmentioning
confidence: 99%